High-strength puncture-resistant composite film

Through multi-layer composite structure and chemical reaction, the problem of poor puncture resistance of geomembrane is solved, and a high-strength puncture prevention effect is achieved to prevent leachate leakage.

CN120396474AActive Publication Date: 2025-08-01SICHUAN JIAHAODA PACKAGING MFG CO LTD

Patent Information

Application Number
CN202510744150.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-05
Publication Date
2025-08-01
Estimated Expiration
2045-06-05

AI Technical Summary

Technical Problem

The geomembranes in the prior art have poor puncture resistance and are prone to puncture, causing leakage of leachate.

Method used

Using a multi-layer composite structure, including a surface protective layer, a first reaction layer, a second reaction layer, a third reaction layer and a bottom protective layer, the curing reaction of cyanoacrylate and aminosilane coupling agent, and the polymerization reaction of imidazole-based ionic liquid, is formed to form a polymer to fix the puncture and prevent leakage of the leachate.

Benefits of technology

The anti-puncture capability of the composite membrane is significantly improved, the puncture process of the puncture is delayed, and the puncture is further retained through gas expansion and polymer extrusion to prevent leachate leakage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120396474A_ABST
    Figure CN120396474A_ABST
Patent Text Reader

Abstract

The invention discloses a high-strength puncture-resistant composite film, and relates to the technical field of composite films, the high-strength puncture-resistant composite film comprises a surface protection layer, a first reaction layer, a second reaction layer, a third reaction layer and a bottom protection layer which are arranged in sequence; the first reaction layer is prepared from nylon 6 and an amino silane coupling agent; the second reaction layer is made of thermoplastic polyurethane, and a containing channel and cyanoacrylate located in the containing channel are arranged in the second reaction layer; the third reaction layer comprises polypropylene, calcium carbonate and imidazolium ionic liquid; when the composite film is punctured, the cyanoacrylate is in contact with the amino silane coupling agent to generate curing reaction, so that a punctured object is fixedly clamped at the position penetrating through the first reaction layer; the imidazolium ions are in contact with the cyanoacrylate to generate polymerization reaction and form a polymer, and the calcium carbonate is in contact with the leachate to release CO2, so that the polymer is forced to be pressed into a puncture hole, and a puncture object is further retained, so that the anti-puncture effect of the composite membrane is relatively good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite membranes, and particularly relates to a high-strength puncture-resistant composite membrane. Background Art

[0002] Due to its high strength, tear resistance and anti-leakage characteristics, the puncture-resistant composite membrane has been widely used in many fields with demanding material performance requirements. For example, the geomembrane laid in landfills needs to prevent the penetration of sharp garbage (metal, glass) from causing leachate to pollute the soil and groundwater. The geomembrane in the prior art has poor puncture resistance and is easily punctured, resulting in leachate leakage.

[0003] The information disclosed in the background art part of this application is only intended to deepen the understanding of the general background art of this application, and should not be regarded as an admission or any form of implication that this information constitutes the prior art known to those skilled in the art. Summary of the Invention

[0004] The main object of the present invention is to provide a high-strength puncture-resistant composite membrane, aiming to solve the technical problem that the geomembrane in the prior art has poor puncture resistance and is easily punctured, resulting in leachate leakage.

[0005] To achieve the above object, the present invention provides a high-strength puncture-resistant composite membrane, which includes a surface protection layer, a first reaction layer, a second reaction layer, a third reaction layer and a bottom protection layer arranged in sequence; the number of the second reaction layers is at least one; the production material of the first reaction layer includes nylon 6 and an amino silane coupling agent; the second reaction layer is made of thermoplastic polyurethane, and a receiving channel and cyanoacrylate located in the receiving channel are arranged inside the second reaction layer; the third reaction layer includes polypropylene, calcium carbonate and imidazole ionic liquid.

[0006] Optionally, the receiving channel includes a main channel and branch channels that communicate with each other; the main channel is distributed in an Archimedes spiral pattern, the number of the branch channels is multiple, and each branch channel extends radially from the center of the main channel; the pitch of the main channel is less than or equal to 5 mm.

[0007] Optionally, the number of the second reaction layers is two and both are located between the first reaction layer and the third reaction layer; the main channels in the two second reaction layers are arranged in a staggered manner, and the branch channels in the two second reaction layers are arranged in a staggered manner.

[0008] Optionally, the apertures of the main channel and the branch channels are the same, and the aperture at the connection of the main channel and the branch channels is smaller than the aperture of the main channel or the branch channels.

[0009] Optionally, the surface protection layer is made of ultra-high molecular weight polyethylene and nano silicon carbide, and a shingled scale structure is provided on the side of the surface protection layer away from the first reaction layer.

[0010] Optionally, a fluoroalkylsilane coating is provided on the surface of the scale structure.

[0011] Optionally, a fiberglass grid is provided inside the first reaction layer.

[0012] Optionally, silver zeolite nanoparticles are provided inside the first reaction layer.

[0013] Optionally, a nano-SiO2 coating is sprayed on the surface of the third reaction layer close to the bottom protection layer.

[0014] Optionally, the production materials of the bottom protection layer include asphalt, waste tire rubber powder, montmorillonite nanosheets and antioxidants.

[0015] The technical solution of the present invention provides a high-strength puncture-resistant composite film. The composite film is laid in a landfill. The surface protection layer is in contact with the garbage, and the bottom protection layer is in contact with the bottom of the landfill. Sharp garbage objects (metal, glass) sequentially penetrate through the surface protection layer, the first reaction layer, the second reaction layer, the third reaction layer and the bottom protection layer. When the puncture object penetrates through the second reaction layer, the cyanoacrylate in the accommodation channel flows to the upper and lower surfaces of the second reaction layer and contacts the first reaction layer and the third reaction layer. The amino silane coupling agent can provide amino groups, and the cyanoacrylate will undergo a curing reaction when contacting the amino silane coupling agent, so that the puncture object is fixed and stuck at the position where it penetrates through the first reaction layer, delaying the puncture process of the puncture object; if the leachate in the landfill flows to the third reaction layer from the puncture hole, the imidazole ions will undergo a polymerization reaction when contacting the cyanoacrylate and form a polymer. The calcium carbonate in the third reaction layer releases CO2 when contacting the leachate, and the gas expansion will squeeze the polymer formed by the cyanoacrylate. The polymer is pressed into the puncture hole to further detain the puncture object, so that the puncture-resistant effect of the composite film is better. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the drawings required for use in the description of the embodiments or the prior art. Obviously, the following drawings are only some embodiments of the present invention. For those of ordinary skill in the art, without creative efforts, other drawings can be obtained according to the structures shown in these drawings.

[0017] Figure 1 It is a schematic structural diagram of the high-strength puncture-resistant composite film in the embodiment of the present invention; Figure 2 is Figure 1 the enlarged view at A in Figure 3 It is a schematic structural diagram of the second reaction layer in an embodiment of the present invention; Figure 4 It is another schematic structural diagram of the second reaction layer in an embodiment of the present invention.

[0018] Icons: 100, surface protection layer; 101, scales; 200, first reaction layer; 300, second reaction layer; 301, accommodation channel; 400, third reaction layer; 500, bottom protection layer. Detailed implementation manners

[0019] Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention.

[0020] It should be noted that all directional indications (such as up, down, left, right, front, back...) in the embodiments of the present invention are only used to explain the relative positional relationship and movement conditions between components in a specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indications will also change accordingly.

[0021] It should be noted that similar reference numerals and letters represent similar items in the following drawings. Therefore, once an item is defined in one drawing, it does not need to be further defined and explained in subsequent drawings.

[0022] In the present invention, unless otherwise clearly defined and limited, terms such as "connection" and "fixation" should be understood in a broad sense. For example, "fixation" can be a fixed connection, a detachable connection, or integrated; it can be a mechanical connection or an electrical connection; it can be directly connected or indirectly connected through an intermediate medium, and it can be the internal connection of two components or the interaction relationship between two components, unless otherwise clearly limited. For those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood according to specific situations.

[0023] In addition, terms such as "horizontal" and "vertical" do not mean that the components are required to be absolutely horizontal or hanging vertically, but can be slightly inclined. For example, "horizontal" only means that its direction is more horizontal relative to "vertical", and does not mean that the structure must be completely horizontal, but can be slightly inclined.

[0024] In addition, if the embodiments of the present invention involve descriptions such as "first", "second", etc., the descriptions of "first", "second", etc. are only for descriptive purposes and should not be construed as indicating or implying their relative importance or implicitly indicating the quantity of the indicated technical features. Thus, the features defined with "first" and "second" may explicitly or implicitly include at least one such feature. In addition, the meaning of "and / or" appearing throughout the text includes three parallel scenarios. Taking "A and / or B" as an example, it includes scenario A, or scenario B, or the scenario where both A and B are satisfied simultaneously. In addition, the technical solutions between various embodiments can be combined with each other, but it must be based on the ability of those of ordinary skill in the art to implement. When the combination of technical solutions results in contradictions or is unable to be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0025] Reference Figures 1-4 , a high-strength puncture-resistant composite film, comprising a surface protection layer 100, a first reaction layer 200, a second reaction layer 300, a third reaction layer 400, and a bottom protection layer 500 arranged in sequence; the number of the second reaction layers 300 is at least one; the production material of the first reaction layer 200 includes nylon 6 and an amino silane coupling agent; the second reaction layer 300 is made of thermoplastic polyurethane, and a receiving channel 301 and cyanoacrylate located in the receiving channel 301 are provided inside the second reaction layer 300; the production material of the third reaction layer 400 includes polypropylene, calcium carbonate, and imidazole-based ionic liquid.

[0026] The composite film is laid in a landfill, the surface protection layer 100 is in contact with the garbage, and the bottom protection layer 500 is in contact with the bottom of the landfill. Garbage sharp objects (metal, glass) sequentially penetrate through the surface protection layer 100, the first reaction layer 200, the second reaction layer 300, the third reaction layer 400, and the bottom protection layer 500. When the puncture object penetrates through the second reaction layer 300, the cyanoacrylate in the receiving channel 301 flows to the upper and lower surfaces of the second reaction layer 300 and contacts the first reaction layer 200 and the third reaction layer 400. The amino silane coupling agent can provide amino groups, and the cyanoacrylate will undergo a curing reaction when contacting the amino silane coupling agent, so that the puncture object is fixed and stuck at the position where it penetrates through the first reaction layer 200, delaying the puncture process of the puncture object; if the leachate in the landfill flows to the third reaction layer 400 from the puncture hole, the imidazole-based ions will undergo a polymerization reaction when contacting the cyanoacrylate and form a polymer. The calcium carbonate in the third reaction layer 400 releases CO2 when contacting the leachate, and the gas expansion will squeeze the polymer formed by the cyanoacrylate, and the polymer is pressed into the puncture hole to further detain the puncture object, making the puncture-resistant effect of the composite film better.

[0027] It should be noted that imidazole-based ionic liquids are dispersed in polypropylene in a "sea-island structure". The imidazole-based ionic liquids act as basic catalysts to trigger the anionic polymerization reaction of cyanoacrylate.

[0028] Cyanoacrylate is liquid at room temperature.

[0029] As an alternative embodiment, in the first reaction layer 200, nylon 6 is used as the matrix material and its proportion can be more than 98%, for example, 98.5%, and the proportion of the amino silane coupling agent can be more than 1%.

[0030] Nylon 6 has high tensile strength and toughness, which can effectively delay the penetration speed of the puncture object and gain time for the release of cyanoacrylate in the second reaction layer 300. In addition, nylon 6 has good tolerance to organic acids and salt ions in the leachate, avoiding interlayer delamination caused by corrosion. Compared with other engineering plastics (such as PEEK), nylon 6 has a lower cost and is easy to process, making it suitable for large-scale production.

[0031] The manufacturing process of the first reaction layer 200 can be as follows: Nylon 6 and the amino silane coupling agent are melt-blended in an extruder, and the temperature can be maintained at 240°C - 260°C, and then extruded into a film by the extruder. Nylon 6 is a high molecular compound formed by the polymerization reaction of the monomer caprolactam. The molecular chain of nylon 6 contains strongly polar amide groups. The siloxane part (-Si-O-) of the amino silane coupling agent has a weak polarity, and there is a compatibility gradient with the polar groups of nylon 6. During the melt-blending and cooling process, the amino silane tends to migrate to the surface of nylon 6 to form an amino-rich layer for reacting with cyanoacrylate.

[0032] As an alternative embodiment, the surface of the first reaction layer 200 can be punched with micropores having a diameter of 50 μm by a CO2 laser. The diameter of the micropores can be 50 μm, and the pore density can be 100 pores / cm², increasing the surface roughness and the specific surface area to improve the contact area between cyanoacrylate and the first reaction layer 200.

[0033] In some other embodiments, the first reaction layer 200 can be placed in a 5% NaOH solution to slightly etch the surface of nylon 6 to form micropores with a diameter of about 50 μm (density 100 pores / cm²).

[0034] As an alternative embodiment, the accommodation channel 301 includes a main channel and branch channels that communicate with each other; the main channel is distributed in an Archimedean spiral pattern, the number of branch channels is multiple and each branch channel radially extends from the center of the main channel; the pitch of the main channel is less than or equal to 5 mm.

[0035] Specifically, the pitch of the main channel can be set as needed, for example, 2 mm; the branch channels can be distributed at intervals of 30° to 45°. Thus, the main channel and the branch channels form a "spider web" structure. When the puncture object passes through the second reaction layer 300, the aperture of the puncture object is larger than the pitch of the main channel. At this time, when the puncture object passes through the second reaction layer 300 from any position, it will puncture the accommodation channel 301, causing the cyanoacrylate in the accommodation channel 301 to be released.

[0036] In some embodiments, the aperture of the branch channel can be 50% to 70% of the aperture of the main channel.

[0037] As an alternative implementation, the number of the second reaction layers 300 is two and both are located between the first reaction layer 200 and the third reaction layer 400; the main channels in the two second reaction layers 300 are arranged in a staggered manner, and the branch channels in the two second reaction layers 300 are arranged in a staggered manner.

[0038] To avoid the situation where when there is only one layer of the second reaction layer 300, the puncture object may pass through the gap between the main channels, resulting in a "blind area" in the puncture, the second reaction layer 300 is set to two layers, and the main channels and the branch channels are arranged in a staggered manner, so that the puncture object can easily puncture the accommodation channel 301.

[0039] In another alternative implementation, the number of the second reaction layers 300 can be one, and the main channel can be a double helix structure, that is, arranged in a clockwise and counterclockwise staggered manner.

[0040] As an alternative implementation, the apertures of the main channel and the branch channels are the same, and the aperture at the connection of the main channel and the branch channels is smaller than the aperture of the main channel or the branch channel, so that the position of the second reaction layer 300 corresponding to the connection of the main channel and the branch channels is thicker, to enhance the thickness of the second reaction layer 300 and avoid the leakage of cyanoacrylate from the accommodation channel 301.

[0041] The raw materials of the second reaction layer 300 include thermoplastic polyurethane (TPU) and cyanoacrylate. The manufacturing process of the second reaction layer 300 can be as follows: Step S301, 3D print a water-soluble PVA material to form a main channel + radial branch channel structure, and obtain a PVA template; Step S202, sandwich the PVA template between two TPU films, and then perform hot pressing (the temperature can be 160 °C and the pressure can be 5 MPa) for fusion to obtain a first prefabricated film; Step S203, immerse the prefabricated film in a 60 °C water bath to dissolve PVA to form a hollow channel, and obtain a second prefabricated film; Step S304, place the second prefabricated film in a vacuum chamber (-0.1 MPa), and inject cyanoacrylate until the channels are filled; Step S305: Seal the perfusion port of the hollow channel with a UV curable glue (such as Loctite 352) to obtain the second reaction layer 300.

[0042] As an alternative implementation, the surface protection layer 100 is made of ultra-high molecular weight polyethylene (UHMWPE) and nano silicon carbide (SiC), and a shingle-like scale structure is provided on the side of the surface protection layer 100 away from the first reaction layer 200.

[0043] Manufacturing process of the surface protection layer 100: Step S101: Melt and blend UHMWPE and SiC in a twin-screw extruder (temperature 200 - 220 °C), and extrude and pelletize. Step S102: Preheat the mold to 180 °C, lay the pellets into the mold with grooves for the scales 101, hot press at 10 MPa for 15 minutes, and demold after cooling and shaping. Step S103: Deposit a nano SiC layer (thickness 10 - 20 μm) on the surface of the scales 101 to obtain the surface protection layer 100.

[0044] The inclination angle of the scales 101 of the surface protection layer 100 can be 25°.

[0045] The surface protection layer 100 is in direct contact with the garbage. When a hard object contacts the inclined surface of the scales 101 of the surface protection layer 100, the lateral component force causes the puncture object to slide, and part of the puncture energy is consumed. When the un-deflected puncture object penetrates the scales 101, non-linear cracks (similar to the anti-impact mechanism of pangolin scales, similar to a Z shape) are formed due to the shingle-like structure, and the crack propagation resistance is increased by 30%. The SiC particles on the surface of the surface protection layer 100 fall off, but the matrix UHMWPE is not completely broken: Energy dissipation: About 40% of the initial puncture kinetic energy is consumed by deflection and crack propagation.

[0046] As an alternative implementation, a fluorosilane coating, such as FAS-17, with a contact angle > 150° is provided on the surface of the scale 101 structure.

[0047] Fluorosilane coatings generally have the following properties: 1. Waterproofness: The fluorosilane coating can effectively prevent water penetration and is suitable for application scenarios that require moisture protection. 2. Oil resistance: The surface of the coating is not easily attached by oil stains, which is convenient for cleaning and maintenance. 3. Chemical resistance: The fluorosilane coating has resistance to a variety of chemical substances and is suitable for use in corrosive environments. 4. Wear resistance: The coating has a high hardness and can resist physical wear, extending the service life of the material.

[0048] As an alternative embodiment, the interior of the surface protection layer 100 can be filled with microencapsulated phase change materials, such as paraffin / fatty acid. The microencapsulated phase change materials absorb heat and store energy during the day and release heat at night, preventing the composite film from aging due to excessive temperature differences. The composite film of this embodiment can be used in engineering projects in cold regions to reduce the film layer peeling caused by freeze-thaw cycles.

[0049] As an alternative embodiment, a glass fiber grid is provided inside the first reaction layer 200. Glass fiber is an excellent inorganic non-metallic material with a wide variety of types. Its advantages are good insulation, high heat resistance, good corrosion resistance, and high mechanical strength. The glass fiber can enhance the tensile strength of the first reaction layer 200.

[0050] As an alternative embodiment, silver zeolite nanoparticles are provided inside the first reaction layer 200.

[0051] Silver zeolite is a composite material made by embedding silver ions into the microporous structure of zeolite. Zeolite itself is a natural or synthetic porous aluminosilicate mineral, and its crystal structure is composed of SiO4 and AlO4 tetrahedrons, forming regular nano-scale pores. Silver ions are fixed on the zeolite framework by ion exchange or chemical loading, endowing the material with unique properties. Silver-containing zeolite can effectively adsorb volatile iodides (such as radioactive iodine in nuclear waste treatment), convert them into silver iodide and fix them inside the zeolite pores, and has a high decontamination coefficient. Research has found that silver in silver-containing zeolite exists in the form of 0.5-valent cations, and its electronic state is unstable. It can destroy bacterial cells through strong oxidation, and it is a low-cost and harmless antibacterial material to the human body.

[0052] In this embodiment, silver zeolite can be used to inhibit the attachment of microorganisms in leachate.

[0053] As an alternative embodiment, the raw materials of the third reaction layer 400 are: polypropylene (PP) particles, calcium carbonate, and imidazole-based ionic liquid. The polypropylene (PP) particles account for 68%, the calcium carbonate is nano-scale and accounts for 30%, and the imidazole-based ionic liquid accounts for 2%.

[0054] The manufacturing process steps of the third reaction layer 400: S401. Mix polypropylene particles, calcium carbonate, and imidazole-based ionic liquid in a mixer (the temperature can be 190°C and the rotation speed can be 50 rpm), and granulate; S402. Put the granulated material into an extruder and extrude it into a film to form the third reaction layer 400; S403. Spray a nano-SiO2 coating on the surface of the third reaction layer 400.

[0055] Although the imidazole-based ionic liquid is dispersed in an island structure, during the process of extrusion into a film, due to the incompatibility of the materials, that is, the incompatibility between the imidazole-based ionic liquid and polypropylene, the imidazole-based ionic liquid may tend to migrate to the surface of the third reaction layer 400 to form a surface enrichment layer.

[0056] When the imidazole-based ionic liquid contacts cyanoacrylate, a polymerization reaction will occur and a polymer will be formed; after the calcium carbonate in the third reaction layer 400 contacts the leachate, CO2 is released, and the gas expansion will squeeze the polymer formed by cyanoacrylate, and the polymer is pressed into the puncture hole to further retain the puncture object.

[0057] As an alternative implementation, the surface of the third reaction layer 400 close to the bottom protection layer 500 is sprayed with a nano-SiO2 coating. The SiO2 coating has a porous structure and its surface is relatively rough, which can guide the cyanoacrylate to laterally diffuse along the coating with the puncture hole as the center, covering a larger pore diameter area. The CO2 gas generated by the reaction of calcium carbonate and the leachate is directionally guided by the SiO2 porous structure to form a "microbubble reinforcement body". SiO2 is a rigid material, and the polymer formed by the contact of the imidazole-based ionic liquid with cyanoacrylate, SiO2 and calcium carbonate form a composite structure of a rigid skeleton-flexible matrix, and the compressive strength is significantly improved.

[0058] As an alternative implementation, the manufacturing material of the bottom protection layer 500 includes asphalt, waste tire rubber powder, montmorillonite nanosheets and antioxidants.

[0059] The viscoelasticity of the asphalt forms an adhesion layer about 0.5 mm thick on the surface of the puncture object, consuming the vibration energy of the puncture object and reducing fatigue damage.

[0060] The waste tire rubber powder particles act as an elastic phase to improve the elastic recovery rate of the asphalt. The sulfur element in the rubber powder reacts with the asphalt free radicals to form a three-dimensional network, further hindering the puncture object.

[0061] The montmorillonite nanosheets are dispersed in the asphalt in a exfoliated state, and the interlayer spacing is expanded to 3-5 nm, forming a "labyrinth effect", and the leachate penetration path is extended by 10 times. In addition, the montmorillonite nanosheets can improve the compressive strength of the asphalt.

[0062] The antioxidant can prevent the oxidation chain reaction of the asphalt; when heat is generated by puncture friction, the antioxidant inhibits the oxidation of the asphalt at high temperature and keeps the asphalt viscoelastic.

[0063] Manufacturing process of the bottom protection layer 500: S501. The waste tire rubber powder is subjected to microwave desulfurization treatment (power 800 W, time 5 minutes) to improve the interfacial compatibility; S502. The desulfurized waste tire rubber powder is immersed in a 5% ethanol solution of silane coupling agent (KH-570) and stirred at 60 °C for 2 hours to obtain activated rubber powder; S503. Disperse montmorillonite nanosheets in deionized water (concentration 5%), add cetyltrimethylammonium bromide (CTAB, 30% of the mass of MMT), and stir at 80 °C for 24 hours to obtain organically modified nano-montmorillonite; S504. Centrifuge and wash until there is no Br - (detected by silver nitrate), grind after drying; S505. Add molten asphalt (180 °C) to a high-speed shear emulsifier (rotation speed 3000 rpm), slowly add activated rubber powder, and continuously shear for 1 hour to obtain an asphalt-rubber powder system; S506. Add the organically modified nano-montmorillonite to the asphalt-rubber powder system, increase the rotation speed to 5000 rpm, and shear for 30 minutes; S507. Cool down to 160 °C, add the pre-dispersed antioxidant, and stir at low speed (500 rpm) for 15 minutes to avoid decomposition at high temperature, obtaining the prefabricated bottom material; S508. Use a blade coater to coat the prefabricated bottom material on the release paper (PET film), and roll press with a cooling roller, controlling the temperature at 25 °C; S509. Cure at room temperature for 48 hours to complete stress relaxation and structural stability, obtaining the bottom protective layer 500.

[0064] Manufacturing process of the composite film: S1. Align the surface protective layer 100 with the first reaction layer 200 and bond them by hot pressing (temperature 180 °C, pressure 2 MPa, time 5 minutes); S2. The second reaction layer 300 and the third reaction layer 400 are interlocked by laser perforation: a. Use a CO2 laser to punch holes with a diameter of 0.5 mm (spacing 5 mm) on the surface of the third reaction layer 400; b. Hot press (temperature 150 °C, pressure 3 MPa) to make the melt of the second reaction layer 300 flow into the holes of the third reaction layer 400, and form an anchor structure after cooling.

[0065] S3. Final five-layer composite: A. Stack the surface protective layer 100, the first reaction layer 200, the second reaction layer 300, the third reaction layer 400, and the bottom protective layer 500 in sequence; B. Hot press (temperature 140 °C, pressure 5 MPa), and control the time at 8 minutes; C. Use a water-cooled roller to roll press on the composite film to quickly cool the temperature of the composite film below 50 °C; D. Edge sealing: Weld along the film edge to form a 10-mm-wide sealing band; coat silicone sealant to prevent leachate from invading between layers from the side.

[0066] The above are only alternative embodiments of the present invention, and do not limit the patent scope of the present invention accordingly. Any equivalent structural transformation made by using the content of the specification and drawings of the present invention under the inventive concept of the present invention, or any direct / indirect application in other related technical fields, is included in the patent protection scope of the present invention.

Claims

1. A high-strength puncture-resistant composite film, characterized in that, It includes a surface protection layer, a first reaction layer, a second reaction layer, a third reaction layer and a bottom protection layer arranged in sequence; the number of the second reaction layers is at least one; the production material of the first reaction layer includes nylon 6 and an amino silane coupling agent; the second reaction layer is made of thermoplastic polyurethane, and a receiving channel and cyanoacrylate located in the receiving channel are arranged inside the second reaction layer; the production material of the third reaction layer includes polypropylene, calcium carbonate and imidazole ionic liquid.

2. The high-strength puncture-resistant composite film according to claim 1, wherein The receiving channel includes a main channel and branch channels that communicate with each other; the main channel is distributed in an Archimedean spiral pattern, the number of the branch channels is multiple and each branch channel radially extends from the center of the main channel; the pitch of the main channel is less than or equal to 5 mm.

3. The high-strength puncture-resistant composite film according to claim 2, characterized in that, The number of the second reaction layers is two and both are located between the first reaction layer and the third reaction layer; the main channels in the two second reaction layers are arranged in a staggered manner, and the branch channels in the two second reaction layers are arranged in a staggered manner.

4. The high-strength puncture-resistant composite film according to claim 2, wherein, The apertures of the main channel and the branch channels are the same, and the aperture at the connection of the main channel and the branch channel is smaller than the aperture of the main channel or the branch channel.

5. The high-strength puncture-resistant composite film according to claim 1, characterized in that, The surface protection layer is made of ultra-high molecular weight polyethylene and nano silicon carbide, and a shingle-like scale structure is arranged on the side of the surface protection layer away from the first reaction layer.

6. The high-strength puncture-resistant composite film according to claim 5, characterized in that, A fluorosilane coating is arranged on the surface of the scale structure.

7. The high-strength puncture-resistant composite film according to claim 1, wherein A glass fiber grid is arranged inside the first reaction layer.

8. The high-strength puncture-resistant composite film according to claim 1, characterized in that, Silver zeolite nanoparticles are arranged inside the first reaction layer.

9. The high-strength puncture-resistant composite film according to claim 1, wherein A nano-SiO2 coating is sprayed on the surface of the third reaction layer close to the bottom protection layer.

10. The high-strength puncture-resistant composite film according to claim 1, wherein The production material of the bottom protection layer includes asphalt, waste tire rubber powder, montmorillonite nanosheets and antioxidants.

Citation Information

Patent Citations

  • Nylon film composite material for outer film of lithium-ion polymer battery

    CN103254633A

  • Aluminum-plastic film and preparation method thereof

    CN115534442A

  • Laminate for packaging, and outer packaging material for vacuum heat insulation material

    JP2019043061A

  • Multi-layer film

    US20170113840A1

Cited By

  • Geomembrane special for salt lake mine and preparation method of geomembrane

    CN121821913A